Teaching Vocabulary Mastery Through Think-Pair-Share Technique to the Efl Students of AMIK Tri Dharma - Vemmy Maidita Nur Aisyiah (Jurnal Kewarganegaraan, 2022)
Abstract This research aims at finding out whether the think-pair-share technique of learning can be applied to develop the vocabulary mastery of the EFL students of AMIK Tri Dharma. The researcher focused the vocabulary mastery with the objectives: 1) to know the meaning of the words; 2) to know the pronunciation of the words; 3) to know the category of the words, and 4) to know how to use the words in sentences or contexts. The subject of this research was 18 EFL students of AMIK Tri Dharma. This was a classroom action research which was done in two months. The researcher applied two cycles during the research. The result of the research shows that the application of the think-pair-share technique can develop the vocabulary mastery of the EFL students of AMIK Tri Dharma. This can be proven by the increase of the score on the test from 53.05 to 60.4 than to 74.7. The treatment was stopped after 88,8% of the group achieved the criteria of success. The application of think-pair-share technique was effective to develop the EFL students’ vocabulary mastery. Keywords: EFL student, Think-pair-share, vocabulary mastery